Biological Characterization of Water Extracts from the Caps and Stalks of White Hypsizygus Tessellatus (Bunapi Shimeji) and Flammulina Velutipes (Enoki) Mushrooms - Ishmael, Ukaegbu Chinonso; Rashid, Shah Samiur (Innovate Publisher, 2017)
Context:Mushrooms have been consumed over the years for nutritional and medicinal values. The emergence of many disease conditions has necessitated studies into other sources of pharmacological agents other than the synthetic and chemical agents. The diversification of the sources of materials for combating human diseases is a better way of combating the issues of drug resistance currently experienced. The biological activities and composition of water extract from the caps and stalks of White Hypsizygus tessellatus (Bunapishimeji), and Flammulina velutipes (Enoki mushroom) were evaluated.Methods:The antioxidant and antibacterial activities were evaluated through their scavenging ability on 1, 1-diphenylpicrylhydrazyl (DPPH), and the inhibition of bacterial growth in vitro, respectively. Results:From the results, the Enoki extractshad the highest phenolic contentcompared to Bunapi shimeji. Enoki extracts, both caps, and stalks showed the highest scavenging activity against DPPH free radicals (>70 % and >60 %, respectively) at the tested concentrations. Bunapi shimeji extracts had the strongest activity against the tested G- organisms. Reduced activity was observed against the tested G+ organisms likely due to cell wall resistance.Gentamycin was used as the standard antibiotic. Conclusion:The outcome of the study showed that the studied mushrooms are good sources of natural antioxidants.